Factors underlying early sexual initiation among adolescents: A Case Study of Mbare District, Harare, Zimbabwe - Moyo, Stanzia; Zvoushe, Alfred (International Multidisciplinary Research Journal, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Early sexual debut among adolescents has become an emerging global concern since it exposes adolescents to a myriad of reproductive health issues such as early marriages, unwanted pregnancies, abortions, sexually transmitted and HIV infections. Rationalising evidence from a survey, focus group discussions and key informant interviews, the study investigated the factors undergirding early sexual debut among adolescents. It was noted that adolescents engage in early sexual inauguration primarily because of the following: poverty; curiosity and experimenting; the absence of duty bearers (parents, grandparents, aunts, uncles, teachers and religious leaders) in the sexuality socialisation process; cultural initiation ceremonies; peer and sibling pressure; media; coercion; and contradictions imbedded in policy. The study thus recommends an integration and active participation of all duty bearers in the socialisation process of adolescents and enforcement of laws in order to reduce the incidences of early sexual debut. This is done with the view of upholding adolescents’ reproductive health and behaviour. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->